Mycophenolate mofetil vs azathioprine for remission maintenance in antineutrophil cytoplasmic antibody-associated vasculitis: a randomized controlled trial - Hiemstra, Thomas; Walsh, Michael; Mahr, Alfred; Savage, Caroline O.; de Groot, Kirsten; Harper, Lorraine; Hauser, Thomas; Neumann, Irmgard; Tesar, Vladimir; Wissing, Karl-Martin; Pagnoux, Christian; Schmitt, Wilhelm; et al. (The journal of the American Medical Association, 2010)
Current remission maintenance therapies for antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) are limited by partial efficacy and toxicity.To compare the effects of mycophenolate mofetil with azathioprine on the prevention of relapses in patients with AAV.Open-label randomized controlled trial, International Mycophenolate Mofetil Protocol to Reduce Outbreaks of Vasculitides (IMPROVE), to test the hypothesis that mycophenolate mofetil is more effective than azathioprine for preventing relapses in AAV. The trial was conducted at 42 centers in 11 European countries between April 2002 and January 2009 (42-month study). Eligible patients had newly diagnosed AAV (Wegener granulomatosis or microscopic polyangiitis) and were aged 18 to 75 years at diagnosis.Patients were randomly assigned to azathioprine (starting at 2 mg/kg/d) or mycophenolate mofetil (starting at 2000 mg/d) after induction of remission with cyclophosphamide and prednisolone.The primary end point was relapse-free survival, which was assessed using a Cox proportional hazards model. The secondary end points were Vasculitis Damage Index, estimated glomerular filtration rate, and proteinuria.A total of 156 patients were assigned to azathioprine (n = 80) or mycophenolate mofetil (n = 76) and were followed up for a median of 39 months (interquartile range, 0.66-53.6 months). All patients were retained in the analysis by intention to treat. Relapses were more common in the mycophenolate mofetil group (42/76 patients) compared with the azathioprine group (30/80 patients), with an unadjusted hazard ratio (HR) for mycophenolate mofetil of 1.69 (95% confidence interval [CI], 1.06-2.70; P = .03). Severe adverse events did not differ significantly between groups. There were 22 severe adverse events in 13 patients (16%) in the azathioprine group and there were 8 severe adverse events in 8 patients (7.5%) in the mycophenolate mofetil group (HR, 0.53 [95% CI, 0.23-1.18]; P = .12). The secondary outcomes of Vasculitis Damage Index, estimated glomerular filtration rate, and proteinuria did not differ significantly between groups.Among patients with AAV, mycophenolate mofetil was less effective than azathioprine for maintaining disease remission. Both treatments had similar adverse event rates.clinicaltrials.gov Identifier: NCT00307645
Gesehen am 10.05.2023